Heart rate agreement between the 20-meter shuttle run test and virtual system in healthy children: a cross-sectional study - Moran, Cristiane A. (BMC Pediatr, 2019)
BACKGROUND: Earlier studies evaluated the physiological responses to video games in children with different clinical conditions; however, no study has compared active video games with an incremental field test in healthy children. The purpose of this study was to verify the agreement between the 20-m shuttle run test (20 m-SRT) and virtual system (VS). METHODS: This is a cross-sectional study of 235 children (9.0 ± 0.8 years, 109 boys). The two tests were performed one week apart and the children were instructed not to engage in any physical exercise or sports in the 24 h preceding each test. Their resting heart rate was monitored for one minute and then throughout the tests. To evaluate the influence of motivation on the 20 m SRT and (VS), at the end of the tests the children were asked to rate their motivation on a scale of zero to 10, zero being “not cool” and 10 “awesome”. Perceived exertion at the end of the tests was assessed using the modified Borg scale. RESULTS: Maximum heart rate (HRmax) did not differ between the 20 m-SRT and VS (194.4 ± 10.2 bpm vs. 193.2 ± 13.8 bpm, respectively). Both tests were similar for intensity > and < 96% HRmax. The children showed greater exertion on the Borg scale and motivation during the VS. The multiple logistic regression model showed that motivation (p = 0.98), sex (p = 0.53), age (p = 0.61), nutritional status (p = 0.65), and speed (p = 0.18) were not predictive factors of the child’s reaching HRmax. CONCLUSION: VS can be used as a tool to evaluate the intensity of maximal exercise tests, given that the percentage of children who achieved HRmax did not differ between the VS and 20 m SRT. The perceived exertion scales were correlated, but only the modified Borg scale correlated with HRmax in the 20 m SRT. The tests are motivational, and most children obtained the maximum VS score.